2012
DOI: 10.1002/cbic.201200265
|View full text |Cite
|
Sign up to set email alerts
|

Rugulactone and its Analogues Exert Antibacterial Effects through Multiple Mechanisms Including Inhibition of Thiamine Biosynthesis

Abstract: Rugulactone is a dihydro-α-pyrone isolated from the plant Cryptocarya rugulosa in 2009. It has been reported to display IkB kinase (IKK) inhibitory activity, as well as antibiotic activity in several strains of pathogenic bacteria. However, its biological targets and mode of action in bacteria have not yet been explored. Here we present enantioselective syntheses of rugulactone and of some corresponding activity-based protein profiling (ABPP) probes. We found that the ABPP probes in this study are more potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
(25 reference statements)
2
28
0
Order By: Relevance
“…Some small molecule inhibitors have been reported and have even demonstrated antibacterial activity of L . monocytogenes associated with inhibition of phosphomethylpyrimidine kinase . Human pyridoxal kinase is the closest related human protein, with 33.9% overall amino acid identity.…”
Section: Resultsmentioning
confidence: 99%
“…Some small molecule inhibitors have been reported and have even demonstrated antibacterial activity of L . monocytogenes associated with inhibition of phosphomethylpyrimidine kinase . Human pyridoxal kinase is the closest related human protein, with 33.9% overall amino acid identity.…”
Section: Resultsmentioning
confidence: 99%
“…SaThiD was shown to be potentially inhibited by Rugulactone (Ru0), a natural product, as well as by its derivatives Ru1 and Ru2, with IC 50 values ranging from 14 to 32 µM (25). In the absence of thiamine in the medium, the MIC observed for Ru1 was four times lower than in the presence of thiamine for Listeria monocytogenes (25), suggesting that the inhibitory effect of Rugulactone is due to ThiD inhibition, although Rugulactone also inhibits other kinases.…”
Section: Thiamin Biosynthesismentioning
confidence: 95%
“…Whether ThiD and ThiE are essential for the ESKAPE pathogens is still an open question to be addressed by further investigation. On a second level, Nodwell et al showed that L. monocytogenes, which is known to uptake thiamine from the environment, is still sensible to Rugulactone and its derivatives Ru1 and Ru2 (25). When grown in a chemical defined media without thiamine, the inhibitory effects of Rugulactone are potentiated with a 4-fold reduction in the MIC (25).…”
Section: Thiamin Biosynthesismentioning
confidence: 99%
“…Interestingly, the S. aureus ThiD enzyme (SaThiD) has a dual role, phosphorylating HMP in the thiamin biosynthesis pathway as well as pyridoxal and pyridoxine in the pyridoxal biosynthesis pathway, with a K M almost 20 times greater for HMP than for pyridoxal and k cat values 3 times faster for pyridoxal (21), suggesting that SaThiD is more efficient as a pyridoxal kinase than as an HMP kinase. SaThiD was shown to be inhibited by Rugulactone, a natural product and, in the absence of thiamine in the medium, the MIC observed for Rugulactone was four times lower than in the presence of thiamine (22), suggesting that the inhibitory effect of Rugulactone is due to ThiD inhibition, although Rugulactone also inhibits other kinases.…”
Section: Thiamin Biosynthesismentioning
confidence: 96%